2017
DOI: 10.1155/2017/5397656
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Joint Loading in Badminton Lunging between Professional and Amateur Badminton Players

Abstract: The knee and ankle are the two most injured joints associated with the sport of badminton. This study evaluates biomechanical factors between professional and amateur badminton players using an injury mechanism model. The aim of this study was to investigate the kinematic motion and kinetic loading differences of the right knee and ankle while performing a maximal right lunge. Amateur players exhibited greater ankle range of motion (p < 0.05, r = 0.89) and inversion joint moment (p < 0.05, r = 0.54) in the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 35 publications
1
40
0
3
Order By: Relevance
“…Some included articles did not report if footwear was standardized. Valldecabres et al (2018) reported that their participants wore their own badminton shoes, whereas Fu, Ren & Baker (2017) , Mei et al (2017) , and Huang et al (2019) provided the same brand and series of badminton shoes used in the experiments. Several included articles utilized the badminton shoes from the Li Ning ( Hu et al, 2015 ; Lam, Ding & Qu, 2017 ; Lund et al, 2017 ; Park et al, 2017 ), Mizuno, and Yonex company ( Hu et al, 2015 ; Wei et al, 2009 ).…”
Section: Review Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Some included articles did not report if footwear was standardized. Valldecabres et al (2018) reported that their participants wore their own badminton shoes, whereas Fu, Ren & Baker (2017) , Mei et al (2017) , and Huang et al (2019) provided the same brand and series of badminton shoes used in the experiments. Several included articles utilized the badminton shoes from the Li Ning ( Hu et al, 2015 ; Lam, Ding & Qu, 2017 ; Lund et al, 2017 ; Park et al, 2017 ), Mizuno, and Yonex company ( Hu et al, 2015 ; Wei et al, 2009 ).…”
Section: Review Contextmentioning
confidence: 99%
“…Range of motion (RoM) was defined as the difference between maximum and minimum angles of the hip, knee, and ankle joints, which were commonly evaluated at lunge, hitting, and recovery phases. Fu, Ren & Baker (2017) measured knee and ankle RoM to identify the differences between amateur and professional athletes. Park et al (2017) investigated peak and changes in shoe bending and torsion angles between the forefoot and rearfoot regions, together with ankle RoM, to examine how forefoot bending stiffness of footwear would influence foot and ankle mechanics.…”
Section: Review Contextmentioning
confidence: 99%
“…The results indicated that the step-in lunge reduced the muscular demands of lunge recovery and the hop lunge produced greater positive power, representing a more efficient lunging method [4]. Lin et al (2017) compared the joint loading during the right forward lunge motion of an underhand net lift between professional and amateur badminton athletes [10]. Their results revealed that professional players exhibited greater knee joint moments in the sagittal plane and frontal plane compared to amateur athletes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al (2017) compared the joint loading during the right forward lunge motion of an underhand net lift between professional and amateur badminton athletes [10]. Their results revealed that professional players exhibited greater knee joint moments in the sagittal plane and frontal plane compared to amateur athletes [10]. To the best of our knowledge, no study has analyzed the lunge movement in different directions or overall footwork performance.…”
Section: Introductionmentioning
confidence: 99%
“…Badminton players most commonly face knee injury, followed by back, ankle joint, thigh, and calf injuries (Goh et al, 2013;Miyake et al, 2016;Reeves et al, 2015;Yung et al, 2007). Studies on badminton movement patterns training have mainly focused on landing strategies when performing the lunge at the net (Fu et al, 2017;Kuntze et al, 2010) and the backcourt jump smash (Kimura et al, 2010;Kimura et al, 2012). Badminton has unilateral strokes, and landing strategies vary across directions of the strokes.…”
Section: Introductionmentioning
confidence: 99%